Performance of reduced fat-reduced salt fermented sausage with added microcrystalline cellulose, resistant starch and oat fiber using the simplex design - Santos, João Marcos dos [UNESP]; Ignácio, Eduardo Oliveira [UNESP]; Bis-Souza, Camila Vespúcio [UNESP]; Silva-Barretto, Andrea Carla da [UNESP] (Elsevier, 2021)
The search for ingredients that improve technological and nutritional aspects of food has been intensified in recent years by both researchers and industry. Thus, the aim of this study was to evaluate fermented sausages with simultaneous reduction of fat (25%) and salt (25% KCl; 75% NaCl) using up to 2% of three different dietary fiber: microcrystalline cellulose (MCC), resistant starch (RS) and oat fiber (OF). Technological and sensory evaluations used the simplex-centroid mixture design. The dietary fiber added did not affect the weight loss, pH values and sensory acceptance. Models were obtained for water activity, lactic acid bacteria, hardness, chewiness and TBARS values. When included in combination the three dietary fiber helped reduce water activity, inclusion of MCC increased the population of lactic acid bacteria, and inclusion of OF with MCC demonstrated an antioxidant effect and improved hardness and chewiness. These dietary fibers are ingredients that can contribute to the development of reduced fat – reduced salt fermented sausage.
Keywords: Dietary fiber; Lactic acid bacteria; Lipid oxidation; Sensory acceptance